The relationship between gingival pigmentation and periodontal health among a cohort of college students residing in Diyala city, Iraq - Ahmed S Mahmood; Ban S Diab; Natheer H AL-Rawi (Journal of Baghdad College of Dentistry, 2025)
Background:  Gingival pigmentation is a type of gum pigment caused by a range of endogenous and exogenous Factors . Melanin granules occur in the oral environment and aid in periodontal integrity by neutralizing reactive oxygen species produced by dento-gingival plaque-induced inflammation in the periodontal micro-environment. Objectives: The purpose of this study was to determine the prevalence of gingival pigmentation and its relation to periodontal health. Materials and methods: This study utilises a comparative cross-sectional design and recruits students between the ages of 19 and 22 from Diyala University's College of Physical Education and Sport Science. Gingival pigmentation, age, and gender were correlated among the participants. In order to quantify the severity of gingival pigmentation, Kumar et al.'s (2012) gingival pigmentation index was utilized. WHO's Community Periodontal Index (CPI) from 1997 was utilized to assess periodontal health.  Results: Gingival pigmentation was present in 9.11% of the cases. Students with healthy gums and calculus were more prevalent in the group with gingival pigmentation, while students with bleeding gums were more prevalent in the group with free gingival pigmentation. Conclusions: Gingival pigmentation may help reduce susceptibility to gingival inflammation.